1997
DOI: 10.2527/1997.75113074x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc repletion with organic or inorganic forms of zinc and protein turnover in marginally zinc-deficient calves.

Abstract: We conducted two experiments using marginally Zn-deficient (-Zn) calves to determine which supplemental chemical form of Zn would most rapidly reverse certain Zn deficiency signs and to determine whether a change in protein turnover had occurred in Zn deficiency. In Exp. 1, 40 crossbred beef heifers were allocated by BW to four groups. The control group received 23 mg Zn/kg diet DM from ZnSO4 supplemented to the -Zn diet (17 mg Zn/kg diet DM). The three other groups received the -Zn diet. After 21 d, based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
5

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 9 publications
2
29
1
5
Order By: Relevance
“…Their dams were supplemented pre partum with vitamins A, D, and E. In our study a significant positive correlation between serum Zn and serum total Ig concentrations was demonstrated. Engle et al (1997) reported a more pronounced cell response in marginally Zn deficient calves supplemented with Zn-Met and Zn-Lys than in calves supplemented with ZnSO 4 . Nemec et al (2014) reported a greater improvement of the immune status in lactating cows receiving organic Zn compared to those supplemented with inorganic Zn, Cu, and Mn sources.…”
Section: Discussionmentioning
confidence: 99%
“…Their dams were supplemented pre partum with vitamins A, D, and E. In our study a significant positive correlation between serum Zn and serum total Ig concentrations was demonstrated. Engle et al (1997) reported a more pronounced cell response in marginally Zn deficient calves supplemented with Zn-Met and Zn-Lys than in calves supplemented with ZnSO 4 . Nemec et al (2014) reported a greater improvement of the immune status in lactating cows receiving organic Zn compared to those supplemented with inorganic Zn, Cu, and Mn sources.…”
Section: Discussionmentioning
confidence: 99%
“…In young calves the addition of 150 or 3 00mg Zn/kg to a control diet containing 65 mg Zn/kg did not affect mitogen-induced blastogenesis, cytotoxicity and IL-2 production by lymphocytes, or phagocytic and bactericidal activity of isolated neutrophils (Kincaid et al 1997). Calves receiving 17 mg Zn/kg diet had a reduced induration response to intradermal injection of PHA compared with Zn-supplemented animals (Engle et al 1997).…”
Section: Zincmentioning
confidence: 99%
“…Valores mĂ©dios obtidos para as concentrações de zinco nos soros (µg/mL) nos grupos suplementados (G1 e G2) e controle (G3) nos diferentes dias ( 0, 90 e 180). Engle et al (1997), ao afirmarem que as fontes de zinco (orgânico e inorgânico) nĂŁo afetaram as concentrações do zinco plasmático em seu estudo. Entretanto, quando bezerros foram suplementados com 500 mg de zinco/ kg, o zinco orgânico teve uma melhor absorção do que o zinco inorgânico, baseado, sobretudo nas maiores concentrações de zinco no plasma, fĂ­gado, duodeno e rins (WRIGHT; SPEARS, 2004).…”
Section: Resultsunclassified
“…Entretanto, quando bezerros foram suplementados com 500 mg de zinco/ kg, o zinco orgânico teve uma melhor absorção do que o zinco inorgânico, baseado, sobretudo nas maiores concentrações de zinco no plasma, fĂ­gado, duodeno e rins (WRIGHT; SPEARS, 2004). Engle et al (1997), registraram os valores de concentração de zinco sangĂĽĂ­neo entre 0,82 ±0,10 µg/mL e 1,07 ±0,38 µg/mL, e concluĂ­ram que dietas deficientes de zinco nĂŁo afetam as concentrações no plasma e fĂ­gado de bezerros.…”
Section: Resultsunclassified